Weather protect insurance: Empowering 138,734 cooperative members to recover from climate-related shocks - Leyte, James Dizon; Aguila, Lea May; Swaans, Cornelis (2024)
An Alliance partnership-developed Weather Protect Insurance (WPI) mechanism generates an eight-fold return on insurance investment, empowering farmers and strengthening agricultural sustainability. WPI enhanced financial resilience for 138,734 cooperative members (80% farmers), across 222 cooperatives in 74 provinces, in the Philippines, ensuring payouts within 10 days of climate events. Among the 600 farmers surveyed in 2024, 81.75% received payouts for insurance, accelerating recovery. While 20.5% adopted climate-smart agricultural (CSA) practices, full adoption could further increase yields and profits by 2%.